KNOWLEDGE MANAGEMENT SYSTEM PADA DIVISI LALU LINTAS ANGKUTAN JALAN DISHUBKOMINFO KOTA PONTIANAK MENGGUNAKAN METODE SPESIFIC ACTION DAN PENDEKATAN AFTER ACTION REVIEW BERBASIS WEB DAN MOBILE APPLICATION - Syarifah Putri Agustini; Mochamad Wahyudi (Universitas Bina Sarana Informatika, 2015)
A good traffic system will create a condusive social condition which results the establishment of order and comfort on the street. To be able in creating a good traffic system. As the result, there is a need of of trained and fast-moving team in handling the traffic matter, in this case is a team responsible in the implementation of the traffic is Dinas Perhubungan Komunikasi dan Informatika Kota Pontianak/Dishubkominfo (Department of Communication and informatics). However, the realization of the implementation of a good traffic system is considered less optimal because of the lack of knowledge distribution among area of institution. The knowledge possessed only by some particular personnels in the form of personal experience. This kind of knowlede is called as tacit knowledge because of its invisible or unmeasured characteristic so that it easily die out or gone. It is the reason that constrain the distribution of knowledge in the area of institution. As the result, it will slow down institution’s performance in serving the people. It needs knowledge management system that can bind the tacit knowledge and document it into an explicit knowledge (visible or measured knowledge) and can be learned by other people which is Knowledge Management System (KMS). The KMS that will be developed is web and mobile application-based by using Specific Action method. Specific Action method used is developed by using After Action Review approach in such a way that it is provided to be able to capture specific action applied by the user to be reviewed further by the expertise and concluded into a new form of knowledge.